Penerapan Framework Laravel Pada Pembangunan Sistem Informasi Profil Desa Sukoharjo - Arif Nugraha Hernanjaya; Yulita Kartika Sari; Nurul Kholisatul ‘Ulya; Rahardian Luthfi Prasetyo (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
The need for information for Sukoharjo Village is still lacking, Sukoharjo Village still provides information and makes complaints using conventional methods. This conventional method causes slow response and lack of monitoring and evaluation from village officials. This research aims to design a website-based Sukoharjo village profile information system. This research uses the waterfall method which starts from the analysis, design, coding and testing stages. Meanwhile, several methods in the data collection process were observation, interviews and literature study. And for the system testing method, black box testing is used with system design using UML (Unified Modeling Language). This village profile information system can disseminate information about Sukoharjo Village, especially about the village, organizational structure, population data and can make complaints online which can be accessed via devices owned by visitors.